PENERAPAN METODE TALAQQI PADA MATA PELAJARAN AL-QUR’AN HADIS DI SDIT AL-ISLAM SINE - Asroriah, Fatimatul (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2023)
This research aims to explore the application of the Talaqqi method in the teaching of Al-Qur'an and Hadith at SDIT Al-Islam Sine. The Talaqqi method involves direct guidance from teachers in reading and understanding the Al-Qur'an and Hadith. The purpose of this study is to analyze the effectiveness of the Talaqqi method in enhancing students' understanding of the Al-Qur'an and Hadith, as well as its impact on memorization and internalization of Islamic teachings.This research adopts a qualitative research design with a case study approach at SDIT Al-Islam Sine. Data were collected through classroom observations, interviews with teachers and students, as well as document analysis related to the curriculum and teaching methods of Al-Qur'an and Hadith.The findings of this research indicate that the application of the Talaqqi method at SDIT Al-Islam Sine has a positive impact on students' understanding of the Al-Qur'an and Hadith. Teachers who are trained in the Talaqqi method are able to deliver the recitation of the Al-Qur'an and explanations of Hadith in a clear and comprehensive manner. This helps students to better understand the meanings and contexts of Islamic teachings.Furthermore, the Talaqqi method also contributes to students' memorization of the Al-Qur'an. Through a structured approach and guided repetition, students are able to effectively memorize verses of the Al-Qur'an. This method also helps students to internalize and apply Islamic teachings in their daily lives.In conclusion, this research concludes that the application of the Talaqqi method in the subject of Al-Qur'an and Hadith at SDIT Al-Islam Sine provides significant benefits. This method is effective in enhancing students' understanding, memorization, and internalization of the Al-Qur'an and Hadith. The recommendation from this research is to continue the implementation of the Talaqqi method at SDIT Al-Islam Sine and provide adequate training and resources for teachers to effectively implement this method